Community-based Civil Society Organizations in the Social Security Dispute: MSSP and FRENASS - Rojas Lizano, Marco Antonio (2024)
This text reviews the experiences of two civil society organizations in their interaction with the Costa Rican state in the context of the dispute over social security, public health and the CCSS. These are the MSSP and FRENASS, which in recent years have carried out a series of actions to defend the free, solidarity-based and universal nature of public health care provided by the State. An interpretative qualitative methodology was used, which included secondary analysis of qualitative data and semi-structured interviews with 15 key participants. Among the main findings is the centrality of this type of organization in the political arena, where their organizational and mobilization strategies are highlighted; it also highlights the importance of citizen political participation for the control of public policies, but at the same time for the positioning of a common solidarity project.